2016
DOI: 10.17221/322/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, fractionation, and chemical characterisation of fucoidans from the brown seaweed Sargassum pallidum

Abstract: Liu X., Liu B., Wie X.L., Sun Z.L., Wang C.Y. (2016): Extraction, fractionation, and chemical characterisation of fucoidans from the brown seaweed Sargassum pallidum. Czech J. Food Sci., 34: 406-413.The fucoidans were obtained by extraction with water and gradient precipitation with different concentrations of ethanol. The main structural characterisations and bioactivities were achieved. Four fractions of water-soluble crude fucoidans with different molecular weights -SPC60, SPC70, SPH60, SPH70 -were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 22 publications
0
6
0
5
Order By: Relevance
“…The step gradient ethanol precipitation method offers convenience over conventional fucoidan purification techniques. However, the technique has not widely been used for fractionating fucoidans except for that in one reported study [7]. The gradient alcohol precipitation method is commonly used in dextran fractionation and less frequently for purifying other polysaccharides such as starch, hemicellulose, glucan, fructan, pectin, arabinan and pullulan [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The step gradient ethanol precipitation method offers convenience over conventional fucoidan purification techniques. However, the technique has not widely been used for fractionating fucoidans except for that in one reported study [7]. The gradient alcohol precipitation method is commonly used in dextran fractionation and less frequently for purifying other polysaccharides such as starch, hemicellulose, glucan, fructan, pectin, arabinan and pullulan [6].…”
Section: Discussionmentioning
confidence: 99%
“…The precipitation is achieved by incorporating organic solvents such as methanol, ethanol, isopropanol, 1-butanol and acetone or concentrated inorganic salts such as ammonium sulfate ((NH 4 ) 2 SO 4 ) and polymerizing agents such as polyethylene glycol (PEG). The use of this method has been previously reported for fractionating fucoidan [7]. The present study was undertaken as a part of a project to investigate possible industrial uses of S. horneri as a sustainable approach for managing its large biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In S. latifolium, Asker et al (2007) isolated three fractions where Glc and GlcA are the major components and Fuc is a minor one, not responding to the classical fucoidan composition. Other atypical polysaccharides were reported in S. pallidum (Liu et al, 2016) carrying high-mannose fucoidans, rich in uronic acids and scarcely sulfated, and in S. thunbergii (Luo et al, 2019), where a fucoidan completely devoid of sulfate groups was reported ( Table 2). Dietrich et al (1995) studied the polysaccharides from Sargassum vulgare, differentiating whole plants and floaters.…”
Section: Fucalesmentioning
confidence: 96%
“…For brown algae, a calcium compound (usually CaCl 2 ) can be introduced to the polysaccharide fraction during extraction to precipitate alginate, and thereby separate laminarin from the alginate fraction, while fucoidan is present in various amounts in both fractions [73]. Sulfated polysaccharides in the supernatant are often precipitated with ethanol, and further purification steps-often repeated extractions in acid followed by precipitation, size-exclusive chromatography, or filtration-can be applied to achieve pure fucoidan [59,60,74]. It has been suggested to always include a benchmark procedure when employing new extraction methods for fucoidan, in order to get better comparisons of fucoidan structures [75].…”
Section: Extraction Of Brown Seaweed Polysaccharidesmentioning
confidence: 99%